New distribution record of matonia foxworthyi Copel. from Mt. Redondo, Dinagat Islands, the Philippines, with insights on its anatomy and ecology - Amoroso, Victor B.; Orias, Pamela Joy F.; Nobleza, Joevina C.; Lagumbay, April Joie D.; Adlaon, Ivy A.; Salolog, Mary Cor S.; Coritico, Fulgent P. (2025)
This paper presents the new distribution range of the endangered Matonia foxworthyi Copel. Reported for the first time in Mindoro and Sibuyan Islands, it is now documented in Mt. Redondo, Dinagat Islands. Some important morpho-anatomical features of M. foxworthyi are round and pubescent basal stipe, glabrous with grooved in the upper stipe, pedate laminae with less than 19 pinnae, weakly falcate pinna-segments and rhizome with circular vascular cylinder changing to C-shaped in stipe. The detailed morpho-anatomical description of M. foxworthyi
is elucidated including its ecology
Keywords: Fern; Mindanao; Matoniaceae